Are multilateral development banks protecting indigenous peoples? A comparative analysis - Antunes, Victoria Villela Nunes (2018)
This thesis compares the stand-alone safeguard policies for indigenous peoples provided by the World Bank, the Asian Development Bank and the Inter-American Development Bank, in order to propose an indigenous peoples policy for the African Development Bank. It starts by exposing which are indigenous peoples’ rights and how different authors perceive the main document that protects such rights – the United Nations Declarations on the Rights of Indigenous Peoples. Subsequently, it discusses which is the role of Multilateral Development Bank in terms of protecting human rights, in order to understand, through a legal point of view, how the responsibilities of such institutions are regarded. Later, the indigenous peoples safeguard policies applied by the 3 above mentioned Banks are compared within them, in order to analyze each of the topics provided by the documents and understand their similarities and differences. The inputs provided by the interviewees are highly constructive to understand some of the weaknesses incorporated not only in the policies, but in some of the Banks’ mechanisms and processes. Some of the weaknesses in the safeguards compliance and the gaps between the written policies and their implementation are also exposed. Finally, this thesis develops a proposal for a standalone indigenous peoples policy for the African Development Bank.